2022
DOI: 10.1177/02601060221090699
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the risk factors of child malnutrition in Sub-Sahara Africa: A scoping review

Abstract: Background: Malnutrition prevents children from reaching their full physical and mental potential. Health and physical consequences of prolonged states of malnourishment among children are: delay in their physical growth and motor development; lower intellectual quotient (IQ), greater behavioural problems and deficient social skills; susceptibility to contracting diseases. According to the 2015 Millennium development goal (MDG) report, sub-Saharan Africa (SSA) accounts for one third of all undernourished child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 39 publications
0
2
0
1
Order By: Relevance
“…Furthermore, within Linxia Prefecture, notable distinctions in the detection rate of malnutrition were observed across different age groups. Among middle school students aged 16 and older (≥ 16), the study identi ed the highest detection rate of malnutrition, aligning with ndings from prior research conducted by Niza [17] and colleagues. This trend highlights the importance of considering age-speci c nutritional interventions and strategies tailored to the distinct needs of students at various stages of adolescence.…”
Section: Discussionsupporting
confidence: 83%
“…Furthermore, within Linxia Prefecture, notable distinctions in the detection rate of malnutrition were observed across different age groups. Among middle school students aged 16 and older (≥ 16), the study identi ed the highest detection rate of malnutrition, aligning with ndings from prior research conducted by Niza [17] and colleagues. This trend highlights the importance of considering age-speci c nutritional interventions and strategies tailored to the distinct needs of students at various stages of adolescence.…”
Section: Discussionsupporting
confidence: 83%
“… 14 Sub‐Saharan Africa accounts for one‐third of all malnourished (protein‐energy malnutrition) children globally. 15 There are about 4.3 million under‐five deaths yearly from malnutrition, accounting for a staggering 21.3% of deaths in this vulnerable age group. 16 Malnutrition is one of the most critical factors that affect patients' risk of infection, length of stay, and prognosis of patients with sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…The World Health Organization (WHO) reported that about 155 million children under 5 years of age are stunted, 52 million are wasted, and 17 million are severely wasted 14 . Sub‐Saharan Africa accounts for one‐third of all malnourished (protein‐energy malnutrition) children globally 15 . There are about 4.3 million under‐five deaths yearly from malnutrition, accounting for a staggering 21.3% of deaths in this vulnerable age group 16 .…”
Section: Discussionmentioning
confidence: 99%
“…Esta variación persistió incluso después del ajuste por los factores de riesgo identificados de cada tipo de desnutrición, se identificaron varios factores de riesgo de desnutrición, incluido el bajo peso al nacer y el estado nutricional materno inadecuado (M. R. K. Chowdhury et al, 2023). Hay mucho margen para reducir la carga de la desnutrición entre los niños menores de 5 años abordando estos factores de riesgo (Simwanza et al, 2023) greater behavioural problems and deficient social skills; susceptibility to contracting diseases. According to the 2015 Millennium development goal (MDG.…”
Section: Factores Relacionados Con El Sectorunclassified